The children's interaction in the do-of-bill games - Ana Carolina Duarte; Débora da Roza Mello (Universidade Federal de Santa Catarina, 2007)
In this article, an experience of supervised apprenticeship is discussed, starting from the participant observation, of the practice of registrations and of the elaboration of intervention proposals with the children and professionals of a regular day care of net of public education of the municipal district of Florianópolis. He is born of an evaluation of the eighth phase of the Course of Pedagogy, tends for objective to analyze the children's interactions in the do-of-bill games. Where did this theme appear from? He leaves of the discussed focus and chosen together among academic, teacher-advisor and the professionals of infantile education of the institution where he/she felt the apprenticeship, "the interactions in the moments of park and feeding", starting from him, we cut out a more little to give visibility to the games and it do-of-counts him/it on these moments.